2018
DOI: 10.1016/j.polymertesting.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Interlaminar fracture toughness of 5HS Carbon/PEEK laminates. A comparison between DCB, ELS and mandrel peel tests

Abstract: The present work focuses on the applicability of the mandrel peel test to quantify the interlaminar fracture toughness of 5 harness satin woven fabric carbon/PEEK composites. For this purpose, the Mandrel Peel (MP) test was compared to the Double Cantilever Beam (DCB) and End-Loaded Split (ELS) test in terms of experimental procedure and obtained results. The interlaminar toughness of the 5 harness carbon/PEEK was measured both parallel and perpendicular to the predominant fibre direction at the interface. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Hine et al [40] have reported that such unstable crack propagation in FRP composites is caused by local regions of high toughness. Thus, when the crack tip reaches a tougher region (for example, due either to a somewhat tougher region of the matrix or to fibre bridging having developed), crack propagation is retarded until the build-up of stored elastic energy becomes sufficient to reinitiate crack propagation [41]. However, upon reinitiation, the stored elastic energy is typically higher than required for stable propagation and the crack now propagates very rapidly in an unstable manner until it runs out of sufficient input energy for further growth and arrests.…”
Section: Mode I Double Cantilever Beam (Dcb) Test Resultsmentioning
confidence: 99%
“…Hine et al [40] have reported that such unstable crack propagation in FRP composites is caused by local regions of high toughness. Thus, when the crack tip reaches a tougher region (for example, due either to a somewhat tougher region of the matrix or to fibre bridging having developed), crack propagation is retarded until the build-up of stored elastic energy becomes sufficient to reinitiate crack propagation [41]. However, upon reinitiation, the stored elastic energy is typically higher than required for stable propagation and the crack now propagates very rapidly in an unstable manner until it runs out of sufficient input energy for further growth and arrests.…”
Section: Mode I Double Cantilever Beam (Dcb) Test Resultsmentioning
confidence: 99%
“…The crack propagation was stable for each specimen. The response of the current ENF specimens is similar to that reported in the literature [17,28]. Mode-II fracture toughness was evaluated based on the compliance calibration method outlined in ASTM D7905 [21].…”
Section: Enf Results or Mode-ii Fracture Toughness Resultsmentioning
confidence: 99%
“…Wear resistance of glass fiber reinforced polymer/ carbon composites were widely improved with the optimum addition of nanofillers. [37][38][39][40][41][42] Scanning electron microscope examination [Cloisites 10A and 20A] under various loading conditions of I.30E [0, 1, 2, 3, and 4 wt%] nanomer was studied. The results showed that the addition of I.30E Nanoclay enhanced the hydrophobicity of the nanocomposite with a maximum improvement of about 40% at 4 wt% of loading.…”
Section: Study About Tensile and Flexural Behavior Glass Fiber Reinfo...mentioning
confidence: 99%